Kebahagiaan Mahasiswa Penghafal Al-Qur’an : Kontribusi Spiritualitas, Kebersyukuran dan Kesabaran - Raiyati, Siti (Faculty of Ushuluddin and Humanities, 2024)
This study aims to examine the relationship of spirituality, gratitude and patience to the happiness of student colleges memorizing the Quran in Pondok Pesantren An Nur Ngrukem Bantul Yogyakarta. The hypothesis in this study is that there is a relationship between spirituality, gratitude and patience to the happiness of student colleges memorizing the Quran. The subject of this study is student colleges who are memorizing the Qur'an at the boarding school An Nur Ngrukem Bantul Yogyakarta amounted to 120 people. This research used is regression analysis that is processed by using SPSS 17 for windows. Regression test results show: 1) There is a relationship between spirituality, gratitude and patience to the happiness of the student colleges memorizing the Qur'an with the coefficient of correlation F = 18.858 with a significance level of 0.000 (p<0.05) which means significant. 2) There is a positive relationship between spirituality with happiness, the value of r = 0.197 with a significance value of 0.032 (p <0.01) which means very significant. 3) There is no relationship between gratitude with happiness, value r = 0.058 with significance value 0.532 (p> 0.05) which means not significant. 4) There is a relationship between patience with happiness, with the value of r = 0.367 with a significance value of 0.000 (p <0.05) which means significant. Spirituality, gratitude and patience jointly affect the happiness of the Qur'an memorizing student colleges. Spirituality and patience are the variables that can affect happiness in a positive direction. The higher the spirituality and patience of the Quran memorizing student colleges the higher their happiness will be. Keywords: Spirituality, Gratitude, Patience, Happiness.